Role of MicroRNAs in Insect Host–Microorganism Interactions - Asgari, Sassan (Frontiers in Physiology, 2011)
MicroRNAs (miRNAs) have appeared as important regulators of various biological processes including development, cancer, immunity and host-microorganism interactions. Accumulating evidence demonstrates the differential expression of host miRNAs upon infection by various microorganisms and the involvement of microorganism-encoded miRNAs in host manipulation. Some of these alterations could be part of a host response to an infection to limit replication and dissemination of the microorganism or, conversely, due to manipulation of the host miRNA pathway by the microorganism to facilitate its replication. Insights into the role of miRNAs in host defence responses and host manipulation by microorganisms will enable a better understanding of host-microorganism interactions.